Fabrication of a composite anion exchange membrane with aligned ion channels for a high-performance non-aqueous vanadium redox flow battery. Issue 9 (30th January 2020) - Kim, Jae-Hun; Ryu, Seungbo; Maurya, Sandip; Lee, Ju-Young; Sung, Ki-Won; Lee, Jae-Suk; Moon, Seung-Hyeon
Abstract : Fabrication of high-conductivity ion exchange membranes (IEMs) is crucial to improve the performance of non-aqueous vanadium redox flow batteries (NAVRFBs). Abstract : Fabrication of high-conductivity ion exchange membranes (IEMs) is crucial to improve the performance of non-aqueous vanadium redox flow batteries (NAVRFBs). In the present work, anion exchange membranes with high-conductivity were fabricated by aligning ion channels of the polymer electrolyte impregnated in porous polytetrafluoroethylene (PTFE) under electric fields. It was observed that the ion channels of the polymer electrolyte were uniformly orientated in the atomic-force microscopy image. Its morphological change could minimize detouring of the transport of BF4 − ions. The results showed through-plane conductivity was improved from 12.7 to 33.1 mS cm −1 . The dimensional properties of the fabricated membranes were also enhanced compared with its cast membrane owing to the reinforcing effect of the substrate. Especially, the NAVRFB assembled with the optimized membrane showed increased capacities, with a 97% coulombic efficiency and 70% energy efficiency at 80 mA cm −2 . Furthermore, the optimized membrane made it possible to operate the NAVRFB at 120 mA cm −2 . Its operating current density was 120 times higher than that of a frequently used AHA membrane for RFBs.